Fostering excellence in sports, recreation, and rehabilitation: Leadership and management in Albanian higher education institutions - Brovina, Fisnik; Shkreli, Lumtor; Bushati, Marsida (Edelweiss Applied Science and Technology, 2024)
Higher education institutions specializing in Sports, Recreation, Adventure Tourism, and Rehabilitation must operate within a dynamic environment characterized by globalization, technological advancements, and piercing changes in social demand. Hence, effective management and leadership have become essential to migration across this domain. This study contextualizes leadership and management research for the SRATR fields while examining the evolution of these fields in higher education. It explores the management and leadership dilemmas within the SRATR industry characterized by diversity, globalization, and technological advancement, offering insights into present opportunities and challenges. This article calls for a flexible approach to both management and leadership; fundamentally promoting creativity, cooperation, and adaptability within the context of sports, leisure, and rehabilitation within the Albanian setting. In addition, it provides recommendations for the enhancement of student experience, diversity & inclusion, technological integration, leadership development, various management strategies, and community participation within Albanian SRATR institutions.